Public transportation in South Tangerang City, Indonesia and Hat Yai City Municipality, Thailand : A comparative study - Meita Triana Indah Puri (Prince of Songkla University, 2013)
Thesis (M.B.A., Public Administration)--Prince of Songkla University, 2012